BEING PIOUS MUSLIMS: Religious Devotion and Radicalism in Indonesia - Imron Rosidi (Asia-Pacific Journal on Religion and Society, 2021)
Islamic groups in Indonesia have used several channels to implement their goals.  The sea of people during the 212 action originating from various regions in Indonesia reflected that political Islam in the Indonesian context needed to be reexamined. Using interview and literatures to get data, this article argued that  Indonesian Muslims have not been radical as assumed. They just have a desire to be pious Muslims. During this time there is a misunderstanding among scholars who are involved in Muslim society and Western politicians who tend to be difficult to distinguish between pious and radical Muslims. The tendency that appears on the surface is their high suspicion of Muslims who have the desire to increase the level of piety in practicing their religion. The 212 action which consists of several volumes, is not threatening religious tolerance in Indonesia. It has nothing to do with the strengthening of Islamic radicalism or the anti-minority movement. The movement was only an accumulation of public piety symptoms of the Islamic community in Indonesia.